Agricultural Training and Its Impact on Food Crop Production in Cameroon - Mbu Daniel Tambi (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2019)
Agricultural training has an important position in agriculture development, food security and poverty alleviation in Cameroon. The objectives of this study are to examine the impact of agricultural training on food crop production; determine the factors influencing agricultural training, decompose the effect of agricultural training type on food crop production, and recommend relevant economic policies on the basis of our analysis. Using data from the 2007 MINADER and data from the 2007 Household Consumption Survey, we used the control function model to estimate our result from STATA 13.0. We observed that the 2SLS, Control Function without interaction and Control Function with interaction results revealed that household agricultural training strongly correlates with food crop production. Also professional, workshop and on the farm training strongly affects agricultural production, with probability points of 2.6, 0.3 and 2.8 percent of increasing agricultural production respectively. Farm training becomes a high priority for increasing agricultural production.   There are considerable opportunities to take advantage of agricultural training in terms of increase in cereal productivity. The decision makers, civil society organizations and stakeholders operating in agriculture should multiply agricultural training in both former and informer training, through the creation of agricultural schools, workshop/seminars and on the field training.  JEL Classification: I25, D13, Q12